Income inequality, health outcomes and financial crisis: novel evidence - Alexiou, Constantinos (ATINER, 2023)
This study revisits the existing relationship between income inequality and population health by subjecting it to a battery of empirical testing using different measures of inequality and health outcomes for 33 high-income OECD countries. Apart from the impact of macroeconomic covariates we also explore the effect of the global financial crisis (2007/8) on health outcomes. For the empirical investigation we have adopted panel cointegration analysis to obtain long-run estimates that are free of endogeneity bias. For robustness we also adopt a panel quantile regression (QR) in an attempt to provide a more detailed picture of the underlying relationships at several points of the conditional distribution. We find that in the long run, income inequality affects adversely population health which is also confirmed by the quantile estimates. The causal dimension however is more ambiguous whilst the global financial crisis is found to have an insignificant impact on health outcomes.
Keywords: population health; income inequality; infant mortality; life expectancy; financial crisis